2007
DOI: 10.1529/biophysj.106.097105
|View full text |Cite
|
Sign up to set email alerts
|

Single GUV Method Reveals Interaction of Tea Catechin (−)-Epigallocatechin Gallate with Lipid Membranes

Abstract: Tea catechins, which are flavonoids and the main components of green tea extracts, are thought to have antibacterial and antioxidant activity. Several studies indicate that lipid membranes are one of the targets of the antibacterial activity of catechins. Studies using a suspension of large unilamellar vesicles (LUVs) indicate that catechin causes gradual leakage of internal contents from LUVs. However, the detailed characteristics of the interaction of catechins with lipid membranes remain unclear. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
178
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(187 citation statements)
references
References 46 publications
8
178
0
1
Order By: Relevance
“…This method was also applied to monitor the effects exerted by different flavonoids on vesicle [18] and giant unilamellar liposome membranes [19]. In the present paper the calcein leakage assay was used to study the impact of a group of newly synthesized genistein derivatives on the liposome membrane permeability.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…This method was also applied to monitor the effects exerted by different flavonoids on vesicle [18] and giant unilamellar liposome membranes [19]. In the present paper the calcein leakage assay was used to study the impact of a group of newly synthesized genistein derivatives on the liposome membrane permeability.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…Several studies investigated the interaction between the two polyphenols and the cell membrane using both artificial membranes (Kajiya et al 2002;Kumazawa et al 2004;Tamba et al 2007;Kamihara et al 2008;Iftime et al 2010) and cell lines (Kanupriya et al 2006;Verstraeten et al 2008) and the results showed that flavonoids induced changes at the cell membrane level that lead to an increased protection against oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Epigallocatechin gallate (EGCG), the major polyphenol component of green tea extract, has been shown to possess several antibacterial activities, such as partitioning the lipid bilayer of the bacterial cytoplasmic membrane (7,19,37,38) and specifically inhibiting the activities of bacterial FabG and FabI reductases (key enzymes in fatty acid synthesis) (42), DNA gyrase (16), and gelatinase (5). Moreover, EGCG has been shown to interfere with the integrity of the cell wall through direct binding to peptidoglycan (43).…”
mentioning
confidence: 99%